Social Resilience and State Fragility in Haiti : Breaking the Conflict-Poverty Trap - Verner, Dorte (World Bank, Washington, DC, 2012)
Haiti is a resilient society whose rural communities in particular have developed coping mechanisms in response to a long history of underdevelopment and poor governance. Like other fragile states, however, Haiti is beset by widespread poverty and inequality, economic decline and unemployment, institutional weakness and corruption, violence, lawlessness, and recurrent conflict. In order for Haiti to achieve development, poverty reduction and conflict prevention, there must be a focus on correcting these issues